Peripheral dentinogenic ghost cell tumor: Evaluation of clinical, histopathologic and radiological findings: Case report [Periferal dentinojenik hayalet hücreli tümör: Klinik, histopatolojik ve radyolojik bulguların deǧerlendirilmesi] - GÜMRÜ TARÇIN, BİRSAY; NAMDAR PEKİNER, FİLİZ MEDİHA; BORAHAN, MEHMET OĞUZ (Turkiye Klinikleri, 2013)
The dentinogenic ghost cell tumor is a rare solid variant of the calcifying odontogenic cyst. A 77-year-old man presented with a gingival mass on the alveolar crest mucosa of canine to first premolar of the right mandibular region. After clinical and radiological examination, the prediagnosis was peripheral ossifying fibroma. An incisional biopsy was performed, and the specimen was submitted for histopathologic evaluation. The lesion was characterized histopatholocially by ameloblastoma-like odontogenic epithelial proliferation, presence of ghost cells and dentinoid material. It was finally diagnosed as peripheral dentinogenic ghost cell tumor after excision with a margin of sound bone. In this report, a rare new case is described and the relevant literature is briefly reviewed. © 2013 by Türkiye Klinikleri.
Keywords: Calcifying; Odontogenic cyst; Odontogenic tumors; Tomography